Viscoelastic, Spectroscopic, and Microscopic Characterization of Novel Bio-Based Plasticized Poly(vinyl chloride) Compound - Mei Chan Sin; Irene Kit Ping Tan; Mohd Suffian Mohd Annuar; Seng Neon Gan (International Journal of Polymer Science)
Plasticized poly(vinyl chloride) (PVC) is one of the most widely consumed commodity plastics. Nevertheless, the commonly used plasticizers, particularly phthalates, are found to be detrimental to the environment and human health. This study aimed to investigate the ability of an alternative greener material, medium-chain-length polyhydroxyalkanoates (mcl-PHA), a kind of biopolyester and its thermally degraded oligoesters, to act as a compatible bioplasticizer for PVC. In this study, mcl-PHA were synthesized by Pseudomonas putida PGA1 in shake flask fermentation using saponified palm kernel oil (SPKO) and subsequently moderately thermodegraded to low molecular weight oligoesters (degPHA). SEM, ATR-FTIR, 1H-NMR, and DMA were conducted to study the film morphology, microstructure, miscibility, and viscoelastic properties of the PVC-PHA and PVC/degPHA binary blends. Increased height and sharpness of tan δmax⁡ peak for all binary blends reveal an increase in chain mobility in the PVC matrix and high miscibility within the system. The PVC-PHA miscibility is possibly due to the presence of specific interactions between chlorines of PVC with the C=O group of PHA as evidenced by spectroscopic analyses. Dynamic viscoelastic measurements also showed that mcl-PHA and their oligoesters could reduce the Tg of PVC, imparting elasticity to the PVC compounds and decreasing the stiffness of PVC.